Recognising scientific entrepreneurship in New Zealand - Menzies, Malcolm (New Zealand Science Review, 2010)
​A widely-held view is that if New Zealand wants to get wealthier, it needs increased productivity. A way of achieving higher productivity is to innovate, and research, science and technology (RS&T) and entrepreneurship are two means (among others) of contributing to innovation (Knuckey et al. 2002; Workplace Productivity Working Group 2004; Hall & Scobie 2006; Smith 2006; Mason & Osborne 2007; Earle 2010). It might be assumed that these two separate factors – science and entrepreneurship – would make an even greater contribution were they combined in some way, and indeed much public policy is aimed at achieving such a combination (Ministry of Research, Science and Technology, MoRST 2007).